Olhares cartográficos das narrativas dos desenhos dos autistas no contexto da inclusão escolar - Santos, Antonia do Nascimento Pereira (2024)
This research aimed to realize, through multiple looks, how the appropriation of knowledge by autistic students happens, based on the narratives of their drawings. By capturing the gestures and movements of students with Autism Spectrum Disorder (ASD) through their drawings, we observe that each creative act of their imagination is driven by lines that intersect itselves, showing their re(invention) of the world, escaping the classifications and protocols that imprison their way of existence, especially in school. The narratives of the drawings demonstrate inventions that do not agree with paths of reproduction of ideas, but rather with creative acts that meet their singularities. This research has a qualitative approach and was developed through cartography, which, as a research method, studies objects of more subjective character and requires the researcher to inhabit in different territories, in the perspective of transform to know. In the production of data, as devices of the study, drawing workshops were carried out with two students with ASD: one from high school and another from the final years of elementary in the state public school system of Feira de Santana - BA. Cartographic research had contributions from authors such as: Alves and Pérez (2018), Deleuze (1988); Deleuze and Guattari (1995), Deligny (2015), Derdyk (1989, 2020), Kastrup (2015), Lopes (2009), Mridèieu (1979) and official documents. The results showed that students find, in drawing and art, the possibility of (re)inventing themselves in a singular way, by the gestures of touching, scratching, writing, narrating and experiencing their worldviews. A school that agrees with the differences intersects with the flexible lines, provoking flight lines in the way of existence of the autistic student through the narratives of their drawings. That is possible.